Fluorescein Leakage within Recent Subretinal Hemorrhage in Pathologic Myopia: Suggestive of CNV? - Lan Mi (Journal of Ophthalmology, 2018)
Purpose. To determine whether fluorescein leakage within subretinal hemorrhage is definitely suggestive of choroidal neovascularization (CNV) by multimodal imaging including optical coherence tomography angiography (OCTA). Methods. Twenty-five consecutive highly myopic patients (25 eyes) with fluorescein leakage within subretinal hemorrhage detected within 1 month were prospectively included. All patients underwent OCTA and spectral-domain optical coherence tomography (SD-OCT). The OCTA and SD-OCT findings at the site of fluorescein leakage were analyzed. In cases of a doubtful diagnosis, indocyanine green angiography (ICGA) was also performed to differentiate myopic CNV from lacquer crack if necessary; all patients were followed up by SD-OCT and/or OCTA for at least 2 weeks. Results. In terms of the site of fluorescein leakage, OCTA revealed an abnormal vascular network in the outer retina and a choriocapillaris slab in 22 out of 25 eyes (88%), which were confirmed to be CNV. However, no high-flow signal was observed in 3 of 25 eyes (12%). In these 3 cases, SD-OCT showed a focal rupture of the retinal pigment epithelium-Bruch’s membrane-choriocapillaris (RPE-BM-CC) complex and a columnar hyperreflective signal of blood originating from defects with a volcanic geyser-like appearance, and no exudative signs were detected. Notably, all ruptures of the RPE-BM-CC complex were located exactly at lacquer crack sites. Moreover, with the absorption of subretinal hemorrhage, ruptures of the RPE-BM-CC complex spontaneously resolved without any intervention. Considering the multimodal imaging appearance and follow-up outcomes, these 3 eyes were eventually diagnosed as simple bleeding associated with lacquer cracks. Conclusions. Dye leakage within recent subretinal hemorrhage on FA could be caused by new-onset lacquer cracks in pathologic myopia. Multimodal imaging including OCTA is helpful to differentiate lacquer cracks from myopic CNV.